Blepharostoma vietnamicum (Marchantiophyta): A New Taxon from Indochina, the Unique Largest Species in the Genus - Vadim A. Bakalin; Anna A. Vilnet; Van Sinh Nguyen; Seung Se Choi (Plants)
Blepharostoma is one of the most ancient extant liverwort genera, within which the genetic diversity is quite high, whereas the morphological diversity, owing to the supposed stasis, is quite low. Unusually large plants of this genus were collected in North Vietnam and are described here as new-to-science species via an integrative approach. The two studied specimens do not reveal variability in the sequenced ITS1-2 nrDNA and trnL-F cpDNA loci, are clearly separated from other species by the level of genetic distances, and maintain a stable position on the reconstructed phylogenetic trees. This species is characterized, in addition to the large overall size of the plants, by larger leaf segment cells and a mixed character of oil bodies (i.e., small homogeneous and larger finely papillose ones within one cell). A description of the new taxon; its diagnostic characteristics; photographs; and discussions regarding its ecology, morphological similarities, and potential distribution are provided.